Conformity behavior in crises: evidence from the COVID-19 epidemic in China - Yao, Yujiao; Liu, Shanshan; Chen, Gaoyu; Yang, Yang; Yang, Jiaxin (Frontiers in Psychology, 2024)
Once a mass health crisis breaks out, it causes concern among whole societies. Thus, understanding the individual’s behavior in response to such events is key in government crisis management. The purpose of this empirical study was to comprehensively characterize the individuals' conformity behavior during the COVID-19 outbreak in China, from perspective the social influence theory. Data were collected in February 2020 using an online survey. The individual’s conformity behavior and new influencing factors were identified. The results revealed that affective risk perception, cognitive risk perception, and individual risk knowledge had a positive significant impact on normative influence. Affective risk perception and individual risk knowledge had a positive significant on informative influence. Cognitive risk perception did not significantly impact informative influence. Informative influence and normative influence had a positive effect on conformity behavior. These results have significant implications for the management behavior of the government.